Frequency of Postpartum Haemorrhage with Intravenous TranexamicAcid versus Placebo in Females Undergoing Caesarean Section at Term - FARZANA LATIF, QURATULAIN ABBAS, (Journal of Fatima Jinnah Medical University, 2018)
Background: Obstetric haemorrhage is an important cause of maternal death and serious morbidity worldwide. Postpartum haemorrhage (PPH) can be prevented by a number of pharmacological agents and surgical procedures which can be use variedly. Among the pharmacological agents Tranexamic acid (TXA) is one of the most important drug that is used to prevent PPH. Thisstudy has been conducted to compare frequency of postpartum haemorrhage with intravenous Tranexamic acid versus placebo in females undergoing caesarean section at term. Objectives: To compare the frequency of postpartum haemorrhage with intravenous Tranexamic acid versus placebo in females undergoing caesarean section at term. Methodology: This trail was carried out at Department of Obstetrics and Gynaecology, unit1, Lahore General Hospital, Lahore. The study was conducted after six months of approval of synopsis. Non-probability purposive technique of sampling was used for this study. Total 120 patients were recruited. Demographic details (name, age, gestational age) were obtained. Then, lottery method was used to divide patients randomly in two groups. The patients were given 1 gm. of intravenous Tranexamic acid in group T. Tranexamic acid was prepared in 20 ml of 5% dextroseby the addition of 1 gm (10 ml) of Tranexamic acid. In group P, placebo was given. Distilled water (10 ml) was added in 20 ml of 5% dextrose to prepare placebo. The injection was given 10 minutes before skin incision. Then females underwent caesarean section. After surgery, patients were shifted to ward and were followed-up there for 2 hours postpartum for assessment of blood loss. If blood loss was ≥500 ml, then PPH was labeled (as per operational definition). Both groups were compared by using chi-square test taking p-value ≤0.05 as significant. Frequency was calculated for parity. Data was stratified for age, parity and BMI to address the effect modifiers. Post-stratification Chi-square Test was used in order to check the significance. P-value <0.05 was taken as significant. Study Design: Randomized Controlled Trial. Setting: Department of Obstetrics and Gynaecology, unit 1, PGMI / Lahore General Hospital, Lahore. Duration: Six months after approval of synopsis (18th June, 2015 to 18thDecember, 2015). Sample Size: Total 120 cases were studied in two groups; Each group consist of 60 cases and it is calculated with 80% power of test, 5% level of significance and taking expected percentage of PPH i.e. 10% with TXA and 28% with placebo in females undergoing caesarean section at term. Results: In this study 63 (52.5%) women who underwent C-Section have blood loss <500 ml, among these 40 patients were from TXA group and 23 patients were from placebo group .In 57 (47.5 %) women postoperative blood loss was >500ml, among these 17 patients were from TXA group and 40 patients belong to placebo group. The study results show that postpartum hemorrhage was significantly less with TXA than placebo (14% versus 33%) respectively, P<0.05. Statistically, two groups were significant different in terms of PPH (p-value=0.000). My hypothesis was clearly accepted according to results that there are less chances of postpartum haemorrhage with intravenous Tranexamic acid as compared to placebo in females undergoing caesarean section at term. Conclusion: Our study results concluded that the postpartum hemorrhage was significantly reduced with Tranexamic acid in comparison with placebo (14% versus 33%respectively).